Enteroviral Meningitis without CSF Pleocytosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Seoul National University and other centers in Korea examined the clinical characteristics of enteroviral meningitis in 390 infants and children; 16-18% were without CSF pleocytosis.